IFN-treated macrophage-derived exosomes prevents HBV-HCC migration and invasion via regulating miR-106b-3p/PCGF3/PI3K/AKT signaling axis - Chen, Jing; Yin, Qi; Xu, Shiheng; Tan, Xiaoqing; Liang, Yu; Chen, Chaohui; Li, Li; Zhang, Tao; Shen, Tao (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundStudies revealed that exosomes from IFN-α-treated liver non-parenchymal cells (IFN-exo) mediate antiviral activity. MiR-106b-3p has been shown to play a paradoxical role in disease progressing from different studies. However, its specific role in HBV-related hepatocellular carcinoma (HBV-HCC) and the underlying mechanism remains unclear.MethodHuh7 cells transient transfected with plasmids of HBV-C2 and B3 were co-cultured with IFN-exo. Cell supernatants were collected to detect miR-106b-3p, HBsAg, HBeAg and HBV DNA levels. Cell proliferation, apoptosis, migration and invasion were analyzed. The putative targets of miR-106b-3p were identified by a dual-luciferase reporter system. The expression of PCGF3, migratory proteins(MMP2/9), and the PI3K/AKT signaling pathway-related proteins were assessed by western blot. The expression of PCGF3 mRNA was quantitative analyzed by using 52 pairs of paraffin-embedded tissues from HCC patients. siRNAs-PCGF3 were used to knocked-down PCGF3 expression.ResultsThe expression of miR-106b-3p was significantly higher in THP-1 cells and supernatants treated with IFN-exo than those untreated. Significantly increased expression of miR-106b-3p and decreased expression of HBsAg and HBV DNA were observed in Huh7-C2/B3 cells treated with IFN-exo. In addition, miR-106b-3p was directly target to PCGF3. Scratch healing assay and transwell assay showed that either IFN-exo or miRNA-106-3p over-expression, or siRNAs-PCGF3 inhibited migration and invasion of Huh7-C2/B3 cells, and subsequently resulted in suppression of p-AKT/AKT and p-PI3K/PI3K. Notably, the expression level of PCGF3 was significantly lower in HBeAg (+)-HCC tumor tissues than HBeAg (-)-HCC tumor.ConclusionIFN-α-induced macrophage-derived miR-106b-3p inhibits HBV replication, HBV- Huh7 cells migration and invasion via regulating PCGF3/PI3K/AKT signaling axis. miR-106b-3p and PCGF3 were potential biomarkers in the prevention and treatment of HBV-HCC.